ICD in Cardiac Sarcoidosis: Variables Associated with Appropriate Therapy, Inappropriate Therapy, and Device Complications - Sebastian Mactaggart; Raheel Ahmed (MDPI AG, 2024)
Introduction: Those with cardiac sarcoidosis (CS) are at risk of sudden cardiac death (SCD), which may be prevented using an implantable cardioverter-defibrillator (ICD). There are limited data available that follow the post-procedural outcomes of patients with cardiac sarcoidosis (CS) who have had an ICD implanted. Areas Covered: This review highlights studies that focused on both appropriate and inappropriate therapies in those with an ICD, as well as device complications in this group. There were several variables, including age, sex, ventricular characteristics, and findings on cardiac imaging that were investigated and discussed as influencing factors in predicting appropriate and inappropriate therapies. Conclusions: Adverse events in those with an ICD and CS have been minimally reported in the literature. Individuals diagnosed with CS are at high risk of ventricular arrhythmia, with comparable rates of appropriate therapy but with a higher incidence of side effects and inappropriate therapy. The younger average age of CS patients in comparison to other ICD cohorts warrants the need for further, large-scale, prospective trials with periodic interim follow-ups focused on those with this condition.